Non-antibiotic Treatment Modalities for Bacterial Vaginosis - Adelia, Sarah; Ardelia, Athaya; Susetiati, Devi A. (Infectious Disorders - Drug Targets, 2024)
Caused by an imbalance in the vaginal microbiome, bacterial vaginosis (BV) is among the most commonly occurring vaginal infections in women of childbearing age. If untreated, BV may have a detrimental impact on the obstetric and gynecological health of an individual. To date, treatment for BV includes a regimen of antibiotics and avoidance of relevant risk factors. Since recurrence and reinfection are frequently observed in patients, pharmaceutical treatment for BV remains ineffective nevertheless. Repeated exposure to antibiotics could precipitate drug-resistant strains. The severity of this problem leads to the emergence of non-antimicrobial therapies. This article aims to provide a review on the types and efficacy of various alternative, non-antimicrobial therapeutic regimens.
Keywords: drug